Copper-catalyzed formal [4+1] annulation of N-propargyl ynamides with diketones - Xu, Hao-Jin; Li, Cui-Ting; Chen, Can-Ming; Chen, Jie; Zhu, Xin-Qi; Zhou, Bo; Ye, Long-Wu (ORGANIC CHEMISTRY FRONTIERS, 2022)
An efficient copper-catalyzed formal [4 + 1] annulation of N-propargyl ynamides with diketones is described. This protocol enables practical and atom-economic synthesis of valuable pyrrole-substituted dioxoles in generally moderate to excellent yields under mild reaction conditions. Thus, two new five-membered heterocycles can be constructed in one step through this vinyl cation chemistry.